Karl Marx - Wood, Allen W. (Arguments of the philosophers., 2004)
Karl Marx explains Marx's views from a philosophical standpoint and defends Marx against common misunderstandings and criticisms of his views. This new edition includes a new chapter on exploitation and a substantial new preface.